Metodelogi Madrasah Fikih dan Analisis Mazhab Fikih Ahli Hadits pada Masyarakat Islam - Yazid Aris Fuadi (Fakultas Dakwah IAIN Jember, 2022)
Because the data obtained is quite difficult to delve deeper into the study of hadith in the new era of Islam in Indonesia, therefore this research will only describe a genealogy sketch of hadith studies in Indonesian society. If the origin is still difficult to find, let alone examine the hadith expert madrasas that are used as references and references by the Indonesian people. This research is a library research (Library Research). The research process is carried out by taking literature studies from literature, books, and from the internet. Meanwhile, regarding the affiliation of the schools of hadith experts, there are several opinions on this matter, for example one of the Islamic jurisprudence madrasas of Imam Muslim hadith experts. It cannot be concluded that Imam Muslim is a follower of Shafi'iyah, Hambaliyah, Malikiyah, Hanafiyah, or even a mujtahid group. But in the writings of Waliyullah ad-Dihlawi, it is stated that Imam Muslim, an-Nasai, Ad-Daruquthni, Al-Baihaqi, and AI-Baghawi are followers of the Shafi'i School. Two models of madrasa fiqh scholars of hadith include: 1) So the fuqaha 'and scholars first, before the science of jurisprudence became a separate branch of science called Qurra'. Hadith expert according to Ibn Khaldun (d. 808 H) is one of the madrasas in understanding fiqh. They are mostly in the Hejaz, in comparison to the ra'yu expert madrasas in Iraq. 2) So, hadith experts are those who follow Imam Malik bin Anas and Imam Shafi'i This is quite reasonable. Hadith experts who lived after Imam Shafi'i (d. 204 H) took a lot of his thoughts in determining what kind of hadith could be used as evidence. So do not be surprised if there are scholars who make the book ar-Risalah by Imam Shafi'i (d. 204 H) as the first book to discuss the science of musthalah hadith. In addition, Imam Shafi'i (d. 204 H) also has the book of Ikhtilaf al-Hadith. No one doubts that Imam Shafi'i (d. 204 H) received the title Nashiru as-Sunnah. Later, there will also be many hadith scholars who follow Imam Shafi'i fiqh. Our tentative conclusion is that Imam Shafi'i (d. 204 H) includes the Imam of the Hijaz Expert after Imam Malik bin Anas, as a representative of the Hadith Expert Fiqh School.